2018
DOI: 10.1111/tbed.12829
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of selected flaviviruses in free-living and captive capuchin monkeys in the state of Pernambuco, Brazil

Abstract: Mosquito-borne diseases such as dengue, yellow fever and, more recently, Chikungunya virus (CHIKV) and Zika virus (ZIKV) have a great impact in the public health. In addition, the presence of such viruses might have an impact on wild animal conservation as well as their possible role as animal reservoir. Here, we performed a serological survey searching for antibodies against a panel of flaviviruses [ZIKV, Dengue virus (DENV), Yellow Fever virus (YFV), West Nile virus (WNV), Saint Louis Encephalitis virus (SLE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 16 publications
2
21
0
4
Order By: Relevance
“…Recently, it has been demonstrated that NHP (from urban/peri-urban areas, free-ranging and captive animals) from Northeastern and Central-western Brazil, presented ZIKV-specific (and other arboviral) neutralizing antibodies. Although, the samples presented low titers of antibodies, it suggested exposure to ZIKV and thus a possible involvement in the establishment of ZIKV sylvatic cycle 47 , 48 . However, caution should be exercised, since flavivirus serology is uninformative in settings where subjects have been exposed to several heterologous flavivirus infections, which reiterates the notion that conclusive evidence requires the detection and/or isolation of ZIKV as well as ability to infect and disseminate in biting primatophilic vectors.…”
Section: Discussionmentioning
confidence: 84%
“…Recently, it has been demonstrated that NHP (from urban/peri-urban areas, free-ranging and captive animals) from Northeastern and Central-western Brazil, presented ZIKV-specific (and other arboviral) neutralizing antibodies. Although, the samples presented low titers of antibodies, it suggested exposure to ZIKV and thus a possible involvement in the establishment of ZIKV sylvatic cycle 47 , 48 . However, caution should be exercised, since flavivirus serology is uninformative in settings where subjects have been exposed to several heterologous flavivirus infections, which reiterates the notion that conclusive evidence requires the detection and/or isolation of ZIKV as well as ability to infect and disseminate in biting primatophilic vectors.…”
Section: Discussionmentioning
confidence: 84%
“…In the present study, we demonstrated that antibodies generated against ZIKV or DENV neutralised or enhanced the entrance of ROCV, SLEV, WNV and ILHV in K562 cells. Serological evidences showed those flaviviruses to be circulating in Brazil 22 , 23 and, considering that DENV and ROCV are endemic, the co-circulation of those viruses represents a risk for the development of severe infections if they spread throughout the country. Extensive in vivo studies should be undertaken to validate the actual potential of successive flavivirus infections for becoming increasingly severe as a result of cross-immunological reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we suspected that the PRNT results of these specific animals were consequences of non-specific virucidal agents, inactivating or reducing viruses' adsorption capacity in the cellular monolayer. In addition to the already known cross-reaction between Flavivirus [24,57,61], this non-specific agent explains the high degree of cross-reactivity with the other virus tested, especially in the hemolyzed samples. This hypothesis was confirmed by ELISA assays, which did not recognize specific immunoglobulins in any of the 13 available sera against any of the tested viruses (ZIKV, DENV, YFV) ( Table 2).…”
Section: Discussionmentioning
confidence: 92%
“…with periodic recaptures for serological and molecular tests. These groups could be useful as sentinels, aiming at the early detection of viral circulation and human protection through the identification of priority areas for vaccination [61], mainly in areas with scant populations of howlers.…”
Section: Discussionmentioning
confidence: 99%